Practical Field Guide. Functional Crop Monitoring for Early Stress Detection: Stomatal Conductance and Infrared Thermography as Key Measurement Tools. - Rinza, J.; Ramírez, D.; Ninanya, J. (International Potato Center, 2021)
Determining the right time for crop irrigation is critical to optimizing water use, and being a fundamental part of a management decision support system. It is important to identify the time (when?) when we must irrigate to save water and do not significantly reduce crop yield, as reported in research carried out at the International Potato Center (CIP). This manual has been prepared for use by students, lecturers/faculties, and researchers interested in early identifying crop stress and seeks to provide a set of tools. CIP recently published those tools with funding from the National Program for Agricultural Innovation (PNIA) and the CGIAR Research Program on Roots, Tubers, and Bananas (RTB). Our scopes have been based on the measurement of the maximum light-saturated stomatal conductance, considered the main indicator of plants’ water status, and its relationship with foliage temperature obtained from thermal images processed using open-access software "TIPCIP" (Thermal Image Processor). We can thus compute the crop's water stress index (CWSI), a variable pointing to the degree of crop water stress and the right time for irrigation. This manual provides a handy summary of procedures recently published in international journals that can be applied practically to other crops and foster research on "Water Saving Agriculture" through ecophysiological tools.